Controllable one-step growth of bilayer MoS2–WS2/WS2 heterostructures by chemical vapor deposition. (14th September 2018) - Zhang, Xiumei; Xiao, Shaoqing; Nan, Haiyan; Mo, Haoxin; Wan, Xi; Gu, Xiaofeng; Ostrikov, Kostya (Ken)
Abstract: Heterostructures of two-dimensional (2D) transition metal dichalcogenides (TMDs) offer attractive prospects for practical applications by combining unique physical properties that are distinct from those of traditional structures. In this paper, we demonstrate a three-stage chemical vapor deposition method for the growth of bilayer MoS2 –WS2 /WS2 heterostructures with the bottom layers being the lateral MoS2 -center/WS2 -edge monolayer heterostructures and the top layers being the WS2 monolayers. The alternative growth of lateral and vertical heterostructures can be realized by adjusting both the temperature and the carrier gas flow direction. The combined effect of both reverse gas flow and higher growing temperature can promote the epitaxial growth of second layer on the activated nucleation centers of the first monolayer heterostructures. By using customized temperature profiles, single heterostructures including monolayer lateral MoS2 –WS2 heterostructures and bilayer lateral WS2 (2L)–MoS2 (2L) heterostructures could also be obtained. Atomic force microscopy, photoluminescence and Raman mapping studies clearly reveal that these different heterostructure samples are highly uniform. These results thus provide a promising and efficient method for the synthesis of complex heterostructures based on different TMDs materials, which would greatly expand the heterostructure family and broaden their applications.